KONDISI SOSIO-HISTORIS JAZIRAH ARAB PRA-ISLAM: Sebuah Analisis Komprehensif Menjelang Turunnya Al-Qur'an - Aguspian; Andi Miswar; Sohrah Sohrah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2025)
This article presents a comprehensive socio-historical analysis of the Arabian Peninsula before the advent of Islam and the revelation of the Qur'an in the 630s CE. Based on a synthesis of archaeological evidence, ancient external records, and early Islamic historical texts, this research aims to delineate the complex and diverse social, economic, political, and religious landscape of the Arabian Peninsula. In contrast to simplified narratives that often portray this period as a monolithic